An ultrasonic inverse scattering imaging technique for defect located at an arbitrary position in the cylindrical material. (July 2020) - Zhou, Hongming; Ji, Xiaoming; Li, Peiyuan
In order to meet the quantitative nondestructive evaluation requirements for a cylindrical material, an ultrasonic inverse scattering technique is proposed to reconstruct the defect located at an arbitrary position in the cylindrical material, which can obtain the quantitative geometrical information of a defect from the backscattering data. In order to overcome the problem of incident wave amplitude variation with the relative position between transducer and defect due to the diffraction effect of ultrasonic transducer, the backscattering signal is corrected before input to the defect reconstruction. Three aluminum cylindrical specimens with elliptical defect or circular defect are prepared for experiments, and the results proved the feasibility and validity of this method.